Multi-Fluorescence Real-Time PCR Assay for Detection of RIF and INH Resistance of M. tuberculosis - Peng, Jingfu; Yu, Xiaoli; Cui, Zhenling; Xue, Wenfei; Luo, Ziyi; Wen, Zilu; Liu, Minghua; Jiang, Danqing; Zheng, Heping; Wu, Hai; Zhang, Shulin; Li, Yao (Frontiers in Microbiology, 2016)
Background: Failure to early detect multidrug-resistant tuberculosis (MDR-TB) results in treatment failure and poor clinical outcomes, and highlights the need to rapidly detect resistance to rifampicin (RIF) and isoniazid (INH) Methods: In Multi-Fluorescence quantitative Real-Time PCR (MF-qRT-PCR) assay, 10 probes labeled with 4 kinds of fluorophores were designed to detect the mutations in regions of rpoB, katG, mabA-inhA, oxyR-ahpC and rrs. The efficiency of MF-qRT-PCR assay was tested using 261 bacterial isolates and 33 clinical sputum specimens. Among these samples, 227 Mycobacterium tuberculosis isolates were analyzed using drug susceptibility testing (DST), DNA sequencing and MF-qRT-PCR assay. Results: Compared with DST, MF-qRT-PCR sensitivity and specificity for RIF-resistance were 94.6% and 100%, respectively. And the detection sensitivity and specificity for INH-resistance were 85.9% and 95.3%, respectively. Compared with DNA sequencing, the sensitivity and specificity of our assay were 97.2% and 100% for RIF-resistance and 97.9% and 96.4% for INH-resistance. Compared with Phenotypic strain identification, MF-qRT-PCR can distinguish 227 Mycobacterium tuberculosis complexes (MTC) from 34 Non-tuberculous mycobacteria (NTM) isolates with 100% accuracy rate. Conclusions: MF-qRT-PCR assay was an efficient, accurate, reliable and easy-operated method for detection of RIF and INH-resistance, and distinction of MTC and NTM of clinical isolates.